Modern trends of development of service sector in Ukraine and in the world - Kuchyn, Sergiy (Management and Entrepreneurship: Trends of Development, 2019)
Рurpose. The purpose of the study is to identify the current trends in the development of services. The subject of the research is current trends in the development of services in Ukraine and in the world.Design/methodology/approach. During the study, the classical methods of scientific knowledge (analysis, synthesis, grouping, graphic method, analytical, forecasting, studying of scientific and statistical sources) were used.Findings. The article investigates modern trends of the sphere of services development in Ukraine and in the world. The service sector is considered as part of the dynamically developing domestic and world economic system. The article concludes that the development of various services depends to a large extent on the influence of the state. Allocation of budgetary funds promotes the development of medical services, education, and culture. However, these services have a limited impact on consumers due to the small amount of resources currently allocated to their maintenance and development in Ukraine. The article describes the classification of types of services on a professional basis and developed a scheme that reveals the interconnection between the components of the service sector and socio-cultural infrastructure.Research limitations/implications. The obtained results and conclusions are the basis for in-depth scientific research of the problems of development of the national and world socio-cultural sphere.Originality/value. Results and conclusions can be used in the development of national economy development programs, in the formation of a modernization strategy for modern economic systems. The practical value of the work consists in the fact that the provisions and practical recommendations make it possible to solve the broken scientific and practical problem, and the results of the research, which are of an applied nature, can have practical application in the activities of enterprises, organizations and service providers.